Study the phenomenon of the occurrence of ectopic cells and their treatment by applying the cathodic protection principle using different media and poles - Ebtihaj Suliaman; Layth Qasem (College of Education for Pure Sciences, 2018)
Corrosion is one of the most serious problems facing the industry, which leads to loss billions of dollars annually. It is a complex problem known widly about it and despite intensive experiments and research is still the issue of erosion it and needs a lot of effort and investigation. A number of tests were conducted that leads the way for the conclusion that occurs from chemistry point of view. it was the reaction occurred in electrochemical cells (electrochemical) .For the purpose of clarifying the phenomenon of cells erosion we have used different poles media and apply the principle of corrosion protection by using sacrifice anode with applying an electric current